Process analysis of the effective utilization of molten slag heat by direct blast furnace cement production system - Purwanto, Hadi; Kasai, Eiki; Akiyama, Tomohiro (The Iron and Steel Institute of Japan, 2010)
This paper principally presents a process analysis of the production systems of blast furnace cement (BFC) based on exergy analysis and its carbon dioxide emission. The analysis was first carried out by using exergy balances of actual operating data in the cement industry. The results revealed that a large sum of net exergy losses was found on the conventional BFC production; this was contrary to the preliminary expectations. In the BFC production, the recovery of the thermal exergy of the molten slag should reduce the total exergy losses by up to 20%. In contrast, the emission of CO2–488.2 kg/ton–in BFC production was ower than 797.5 kg/ton emission in portland cement production; this was because portland cement consumes more carbonaceous fuels such as coal. In conclusion, to reduce exergy loss, save energy and minimize CO2 emission, it is imperative that the BFC production process should be improved with the recovery of the thermal exergy of the molten slag, e.g. the direct mixing of raw material of limestone with molten slag is an innovative and attractive solution because limestone can be easily decomposed by sensible heat of the molten slag. This means thermal combination of portland cement and BFC for the effective use of waste heat, in which waste heat in the conventional BFC process is recovered and used for limestone decomposition in the clinker production to produce BFC.